Learn Xcode Tools for Mac OS X and iPhone Development - Piper, Ian (Apress : Imprint: Apress, 2009)
This book will give you a thorough grounding in the principal and supporting tools and technologies that make up the Xcode developer tools suite. Apple has provided a comprehensive collection of developer tools, and this is the first book to examine the complete Apple programming environment for both Mac OS X and iPhone. Comprehensive coverage of all the Xcode developer tools Additional coverage of useful third-party development tools Not just a survey of features, but a serious examination of the complete development process for Mac OS X and iPhone applications.